2014
DOI: 10.1093/rheumatology/ket462
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab vs mycophenolate and vs cyclophosphamide pulses for induction therapy of active lupus nephritis: a clinical observational study

Abstract: RTX seems to be at least as effective as MMF and CYC pulses in inducing remission. Considering that patients treated with RTX had more negative renal prognostic factors, this drug should be considered a viable alternative for the treatment of active LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 36 publications
1
55
1
7
Order By: Relevance
“…Small study size, lack of robust design, and shortterm follow-up are further limitations of RTX clinical trials. These "missing pieces in the jigsaw" call for further large well-designed trials with longer follow-up periods given that the data from a long-term follow-up study by Moroni et al showed promising complete remission after 2 years of follow-up in a significant number of patients (68).…”
Section: Discussionmentioning
confidence: 99%
“…Small study size, lack of robust design, and shortterm follow-up are further limitations of RTX clinical trials. These "missing pieces in the jigsaw" call for further large well-designed trials with longer follow-up periods given that the data from a long-term follow-up study by Moroni et al showed promising complete remission after 2 years of follow-up in a significant number of patients (68).…”
Section: Discussionmentioning
confidence: 99%
“…С одной стороны, в единичных слу-чаях, а также при анализе серии клинических наблю-дений показана эффективность препарата у пациентов с очень высокой активностью СКВ, резистентных к пред-шествующей терапии и высоким риском летального исхода [38][39][40]. С другой стороны, в немногочисленных ретроспективных исследованиях нет указаний на суще-ственное превосходство схем с применением ритукси-маба по отношению к схемам лечения без него [41,42]. Кроме того, в исследовании по изучению эффективности различных протоколов терапии люпус-нефрита на про-тяжении 12 мес не выявлено превосходства включения в лечение ритуксимаба по сравнению с использованием мофетила микофенолата и внутривенного циклофосфа-мида [39].…”
Section: обмен опытомunclassified
“…В исследовании G. Moroni и соавт. не выявлено раз-личий в динамике снижения индекса SLEDAI в группах взрослых пациентов с волчаночным нефритом, получав-ших ритуксимаб, микофенолат и циклофосфамид [41].…”
Section: обмен опытомunclassified
“…Los estudios "de la vida real" [92][93][94][95][96][97][98][99][100] , en su mayoría de cohortes, muestran resultados diferentes al estudio LUNAR; la mayoría de los pacientes incluidos recibieron RTX por falla al manejo inmunosupresor, algunos en combinación con MMF o CFM y otros como monoterapia. La principal conclusión de estos estudios es que RTX estaría indicado en casos refractarios de NL proliferativa.…”
Section: Tratamientounclassified